Analisis Kesulitan Siswa dalam Memahami Konsep Hukum-Hukum Dasar Kimia (Systematic Review) - Sihaloho, Takeshi; Sidauruk, Suandi; Anggraeni, Maya Erliza (FKIP Universitas Palangka Raya, 2024)
This study aims to describe and summarize the results of analyses on students' difficulties in understanding the concepts of fundamental laws of chemistry. The research employs a systematic review method. The sample consists of theses related to students' difficulties in understanding the concepts of fundamental laws of chemistry. Data collection was carried out using documentation techniques by searching and gathering thesis documents, selecting theses for analysis, and determining the research data to be analyzed. The results of the study indicate that students' difficulties in understanding the concepts of fundamental laws of chemistry are as follows: (1) The findings from FY-22 reveal more student difficulties compared to YM-16 and NS-22. (2) In chemical reactions, students assume that the total mass of substances before the reaction changes or is not equal to the total mass of substances after the reaction. Students believe that determining the mass of reaction products is done by summing the mass ratios of the elements without considering the remaining substances, causing the mass ratios of the elements to vary. (3) Students think that the mass ratio of elements forming more than one compound is not fixed and is not a simple whole number. (4) Students assume that determining the volume ratio is based on indices and by summing the coefficients of the reaction equation. (5) Students believe that the forming elements in a reaction have the same volume ratio and that the volume of reacting gases is equal to the mass of the gases involved in the reaction. (6) These findings emphasize the need for targeted strategies to address these conceptual misconceptions in teaching fundamental laws of chemistry.